Acrylate resins, powder coating compositions and powder-coated substrates containing the same

By using the combination of thermosetomic epoxy function (methyl) acrylate resin and specific monomers, the problem of insufficient silk corrosion of pink coating on metal substrates such as aluminum wheels in the existing technologies has achieved high resistance Corrosive and good attachment powder.

CN116635487BActive Publication Date: 2025-01-28AKZO NOBEL COATINGS INT BV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202180086782.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-12-28
Filing Date
2021-12-20
Publication Date
2025-01-28
Estimated Expiration
2041-12-20

AI Technical Summary

Technical Problem

It is difficult to form a powder coating on a metal substrate such as aluminum wheels that have improved filamentous corrosion resistance without damaging transparency or adhesion.

Method used

The thermosettic epoxy function (methyl) acrylate resin is used as the main ingredient. The resin contains epoxy official energy unsaturated monomers, (methyl) acrylic alkyl ester monomer, ethylene -based dilate monomer, ethylene, and ethylene The Jifang monomer and sorcharide monomer, through specific ratio and cross -linked agent, forms a composition suitable for powder coatings.

Benefits of technology

The formation of pink coating with improved silk tolerance and CASS corrosion, transparentness, and good wet adhesion on the formation of metal substrates such as aluminum wheels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004296884290000052
    Figure BDA0004296884290000052
  • Figure BDA0004296884290000131
    Figure BDA0004296884290000131
  • Figure BDA0004296884290000141
    Figure BDA0004296884290000141
Patent Text Reader

Abstract

The present invention relates to a thermosetting epoxy functional (meth)acrylate resin which, when formulated into a powder coating composition, applied and cured to form a powder coating on a metal substrate, provides excellent filiform corrosion resistance without compromising powder coating clarity or wet adhesion.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] Disclosed herein are thermosetting epoxy-functional (meth)acrylate resins and powder coating compositions containing the same. When the thermosetting epoxy-functional (meth)acrylate resins are formulated into powder coating compositions, applied and cured to form a powder coating on a substrate such as a machined aluminum automotive wheel, the powder coating provides excellent filiform corrosion resistance without compromising powder coating clarity or wet adhesion.

[0002] background

[0003] Exposed portions of metal wheels can be worn away by grit and other debris from the road. A hard and tough film is needed to protect the metal wheel surface. The film should be non-porous and should exhibit excellent adhesion to the metal. These properties prevent the spread of corrosion at the film-metal interface. However, the appearance of filiform corrosion, such as visible pitting of the coating, is not necessary for filiform corrosion to grow. Conventional acrylic and polyester protective clearcoat powder coatings of comparable film thickness on aluminum wheels exhibit filiform corrosion over time, even though the coating appears acceptable.

[0004] Clearcoats for aluminum wheels are typically applied over a self-assembled monolayer (SAM or SAM+) wheel surface pretreatment. Pretreating the surface with SAM or SAM+ can maintain the bright color and appearance of aluminum without the incorporation of chromium-containing compounds. However, a clearcoat applied over a SAM / SAM+ pretreatment may still not provide adequate filiform corrosion resistance. A polyester clearcoat applied over pretreated aluminum wheels and interior trim can provide adequate filiform corrosion resistance if the clearcoat is covered with a liquid coating to provide adequate chemical resistance, scratch resistance, and weathering resistance.

[0005] Epoxy-containing acrylic powder compositions are also known. U.S. Patent Nos. 5,407,707 and 5,663,240 (Simeone et al.) disclose powder coating compositions comprising epoxy-functional acrylate polymers. These compositions can provide acceptable appearance when applied over a color coating, but lack acceptable weatherability.

[0006] US 9,834,634 and US 8,716,367 disclose a powder coating composition providing resistance to filamentous and CASS (copper accelerated acetic acid salt spray) corrosion, comprising a thermosetting epoxy functional acrylic resin, the resin comprising a specific amount of epoxy functional unsaturated monomers, hydrophobic acrylic monomers, nonionic monomers different from the hydrophobic acrylic monomers as copolymerized monomers. The powder coating composition may additionally comprise one or more second resins such as a second thermosetting epoxy functional acrylic resin, a copolymerization product of one or more carboxylic acid functional monomers and one or more nonionic comonomers, a copolymerization product of one or more phosphoric acid functional monomers and one or more nonionic comonomers, and mixtures or combinations thereof. However, there is a need for a resin suitable for a powder coating composition having improved resistance to filamentous corrosion on aluminum, wrought alloy or metal substrates without compromising the transparency or adhesion of the powder coating, especially in powder coatings for aluminum or wrought alloy wheels and automotive interiors pretreated with, for example, a hexavalent chromium-free pretreatment.

[0007] Overview

[0008] The inventors have now developed a powder coating composition which, when applied and cured to form a powder coating on a substrate (a metal substrate such as aluminum), provides improved filiform corrosion resistance without compromising powder coating clarity or wet adhesion.

[0009] The present invention relates to a thermosetting epoxy functional (meth)acrylate resin, comprising the following monomers as copolymerized monomers:

[0010] i) about 10 to 40 weight percent epoxy-functional unsaturated monomer;

[0011] ii) about 10-20% by weight of alkyl (meth)acrylate monomers, wherein the alkyl group contains a minimum of 6 carbon atoms,

[0012] iii) about 30 to 70 weight percent of alkyl (meth)acrylate monomers, wherein the alkyl group contains 1 to 5 carbon atoms,

[0013] iv) about 0.5 to 40% by weight of a dialkyl vinylphosphonate monomer,

[0014] v) about 1 to 50 weight percent vinyl aromatic monomer, and

[0015] vi) about 0-0.4% by weight of phosphonic acid monomers,

[0016] The weight percent of each monomer is based on the total weight of copolymerized monomers in the resin.

[0017] The present invention also relates to a powder coating composition comprising the thermosetting epoxy functional (meth)acrylate resin and a crosslinking agent capable of crosslinking with the resin, and a coated substrate coated with the powder coating composition.

[0018] The powder coating composition of the present invention is suitable for coating bare or untreated metal surfaces. The powder coating composition can be used to protect metal surfaces exposed to corrosive or abrasive environments. The powder coating composition can be used to coat cast or forged aluminum or aluminum alloy substrates, such as wheels or interior trim of vehicles.

[0019] Detailed description

[0020] Thermosetting epoxy functional (meth)acrylate resins can provide improved resistance to filamentation and CASS corrosion and can be used in clearcoat or pigmented clearcoat powder coatings.

[0021] The present invention relates to a thermosetting epoxy functional (meth)acrylate resin, comprising the following monomers as copolymerized monomers:

[0022] i) about 10 to 40 weight percent epoxy-functional unsaturated monomer;

[0023] ii) about 10-20% by weight of alkyl (meth)acrylate monomers, wherein the alkyl group contains a minimum of 6 carbon atoms,

[0024] iii) about 30 to 70 weight percent of alkyl (meth)acrylate monomers, wherein the alkyl group contains 1 to 5 carbon atoms,

[0025] iv) about 0.5 to 40% by weight of a dialkyl vinylphosphonate monomer,

[0026] v) about 1 to 50 weight percent vinyl aromatic monomer, and

[0027] vi) about 0 to 0.4 weight percent phosphonic acid monomers, wherein the weight percent of each monomer is based on the total weight of copolymerized monomers in the resin.

[0028] As used in the present specification and claims, the terms "a" or "an" mean "one or more". Thus, "an epoxy-functional unsaturated monomer" means one or more epoxy-functional unsaturated monomers, and similarly, "an alkyl (meth)acrylate monomer" means one or more alkyl (meth)acrylate monomers.

[0029] The term "(meth)acrylate" refers to acrylate or methacrylate. The term acrylate also includes methacrylate. The term "(meth)acrylic" refers to acrylic or methacrylic.

[0030] Suitable epoxy-functional unsaturated monomers i) may include one or more α,β-ethylenically unsaturated carboxylic acids such as glycidyl esters of (meth)acrylic acid, maleic acid or itaconic acid and allyl glycidyl ether. Preferably, the epoxy-functional monomer is selected from the formula H2C=C(R 8 )C(O)OR 9 (Meth) glycidyl acrylate monomer, wherein R 8 is H or lower alkyl and R 9 is a branched or unbranched alkylene residue containing 1 to 4 carbon atoms terminated by a glycidyl group, i.e. the glycidyl ring is located at the distal end of the unsaturation. Exemplary compounds within the definition of formula (I) are glycidyl acrylate, glycidyl (meth)acrylate and 1,2-epoxybutyl acrylate, preferably glycidyl (meth)acrylate of the above formula, wherein R 8 is methyl and R 9 is a glycidyl methylene group. The glycidyl (meth)acrylate monomer may comprise a mixture of monomers of Formula I. Glycidyl (meth)acrylate may be commercially available from The Dow Chemical Company (Midland, MI) or the glycidyl (meth)acrylate monomer may be prepared under reaction conditions conventional to those skilled in the art.

[0031] The amount of epoxy-functional unsaturated monomer i) in the thermosetting epoxy-functional (meth)acrylate resin is in the range of about 10-40 weight percent based on the total weight of copolymerized monomers in the epoxy-functional (meth)acrylate resin. In another embodiment, the amount of epoxy-functional unsaturated monomer i) in the thermosetting epoxy-functional (meth)acrylate resin is in the range of about 20-35 weight percent. If the amount of the epoxy-functional unsaturated monomer is less than about 10 weight percent, it will not measurably contribute to the improvement of solvent resistance and mechanical strength. On the other hand, if the amount exceeds about 40 weight percent, no additional improvement in corrosion resistance is obtained.

[0032] Suitable (meth) alkyl ester monomers ii) are C6-C 15 Alkyl ester monomers, for example, monomers selected from isobornyl (meth)acrylate, dicyclopentadienyl (meth)acrylate, dihydrocyclopentadienyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, cyclohexyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, eicosyl (meth)acrylate, cetyl (meth)acrylate, tridecyl (meth)acrylate, benzyl (meth)acrylate, phenyl (meth)acrylate, or combinations thereof. Such monomers improve the filiform corrosion resistance of weathering coatings on aluminum, such as aluminum wheels.

[0033] Preferred (meth) alkyl ester monomers ii) are bicycloalkyl (meth) acrylates and branched alkyl (meth) acrylates. Preferred bicycloalkyl (meth) acrylates are dicyclopentadienyl (meth) acrylate and isobornyl (meth) acrylate, most preferably isobornyl (meth) acrylate. Preferred branched alkyl (meth) acrylate is 2-ethylhexyl (meth) acrylate. For example, the (meth) alkyl ester monomer ii) may comprise a bicycloalkyl (meth) acrylate, such as isobornyl (meth) acrylate, or a branched alkyl (meth) acrylate, such as 2-ethylhexyl (meth) acrylate.

[0034] The (meth)acrylate monomer ii) may also have a mass solubility in water of 3.5 g / L or less, in another embodiment preferably 2.5 g / L or less and itself forms a glass transition temperature (T g ) in the range of 50-175°C, and in another embodiment preferably in the range of about 65-175°C. The term "mass solubility" refers to the solubility of the homopolymer using Advanced Chemistry Development (ACD / Labs) software The calculated solubility in water of a given material is determined and is available in the Chemical Abstracts' Registry.

[0035] In some embodiments, the (meth)acrylate monomer ii) may be free or substantially free of hydroxyl functional groups.

[0036] The amount of the alkyl (meth)acrylate monomer ii) in the thermosetting epoxy functional (meth)acrylate resin is in the range of about 10-20 wt % based on the total weight of copolymerized monomers in the epoxy functional (meth)acrylate resin.

[0037] The (meth)acrylic acid alkyl ester monomer iii) may comprise one or more (meth)acrylic acid C1-C5 alkyl esters, such as methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, pentyl (meth)acrylate, neopentyl (meth)acrylate and mixtures thereof. Preferably, the comonomer iii) comprises one or more monomers selected from methyl methacrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate or combinations thereof.

[0038] The (meth) alkyl acrylate monomer iii) may also be referred to as a “nonionic monomer.” Nonionic monomers do not have acidic groups or salts, basic groups or salts, polyactive hydrogen (polyahl) groups (eg, OH, SH, NH), or condensation crosslinking groups.

[0039] The alkyl (meth)acrylate monomer iii) is different from the alkyl (meth)acrylate monomer ii).

[0040] The alkyl (meth)acrylate monomer iii) may have a mass solubility in water of 30 g / L or less or preferably 25 g / L or less. The alkyl (meth)acrylate monomer iii) may contain no or substantially no hydroxyl functional groups.

[0041] The vinylphosphonic acid dialkyl ester monomer iv) may comprise one or more phosphonic acid di-C1-C6 alkyl ester monomers. The C1-C6 alkyl group may be a linear, branched or cyclic alkyl group. Preferably, the vinylphosphonic acid dialkyl ester monomer is a phosphonic acid di-C1-C4 alkyl ester monomer. The vinylphosphonic acid dialkyl ester monomer may have a structure as shown in Figure 1, wherein each R is independently a C1-C6 alkyl group, preferably a C1-C4 alkyl group, most preferably a methyl group or an ethyl group.

[0042]

[0043] Most preferably, the dialkyl vinylphosphonate monomer comprises a dimethylphosphonate monomer (wherein both R groups are methyl).

[0044] Vinylphosphonic acid dialkyl ester monomer iv) is different from phosphonic acid monomer v). It is known in the art that phosphonic acid can improve the adhesion of certain polymer resins to metal substrates. Some literature teaches the preparation of copolymers with phosphonic acid monomers. Vinylphosphonic acid monomers have a structure as described above for Figure 1, except that at least one of the R groups is H. However, contrary to the prior art teachings of preparing copolymers with phosphonic acid monomers, the inventors have found that if the thermosetting epoxy-functional (meth)acrylate resin of the present invention contains a phosphonic acid functional monomer as one of the monomers, the phosphonic acid group reacts with other functional groups in the thermosetting epoxy-functional (meth)acrylate resin, causing gel formation and / or insoluble residue formation during the polymerization process. This makes the resulting polymer unsuitable for use in coating compositions. Therefore, the phosphonic acid functional groups built into the copolymer should be minimized, preferably completely avoided. Without wishing to be bound by theory, the inventors believe that the presence of both phosphonic acid and glycidyl groups in the polymer mixture leads to the undesirable formation of very high molecular weight polymer materials - including thermosetting polymer network materials - during the polymerization process.

[0045] The amount of phosphonic acid monomer iv) in the thermosetting epoxy functional (meth)acrylate resin is in the range of 0-0.4 wt %, more preferably 0-0.2 wt %, most preferably 0 wt %, i.e. the thermosetting epoxy functional (meth)acrylate resin does not contain a phosphonic acid monomer (e.g. a phosphonic acid monomer) as a copolymerized monomer.

[0046] Suitable vinyl aromatic monomers v) contain at least 6 carbon atoms. Preferably, the vinyl aromatic monomers v) are selected from styrene, α-methylstyrene, α-ethylstyrene and other α-alkyl substituted styrenes, vinyltoluene, divinylbenzene and mixtures thereof. Most preferably, the vinyl aromatic monomers vi) comprise styrene.

[0047] The amount of the vinyl aromatic monomer v) in the thermosetting epoxy functional (meth)acrylate resin is in the range of about 1-50 wt % based on the total weight of the copolymerized monomers in the thermosetting epoxy functional (meth)acrylate resin. In one embodiment, the amount of the vinyl aromatic monomer v) is in the range of about 0.5-12 wt % of the vinyl aromatic monomer v) based on the total weight of the copolymerized monomers in the thermosetting epoxy functional (meth)acrylate resin.

[0048] As can be seen from the examples herein, the thermosetting epoxy functional acrylate resin can have a T greater than 40°C. g Preferably, the thermosetting epoxy functional acrylate resin has a T greater than 50°C. g . Keep T appropriately high g Ensure adequate anti-blocking or packaging stability while maintaining adequate flow and film-forming properties.

[0049] In one embodiment, the powder coating composition comprises a thermosetting epoxy functional acrylate resin of the present invention having a Tg greater than 50°C.

[0050] In another embodiment, the powder coating composition comprises two different thermosetting epoxy functional acrylate resins of the present invention, both resins having a Tg greater than 40° C. Preferably one resin has a Tg greater than 50° C.

[0051] Any reference to Tg (glass transition temperature) herein is the Tg measured by differential scanning calorimetry (DSC). Differential scanning calorimetry (DSC) is a thermal analysis technique that studies how the heat capacity (Cp) of a material changes with temperature. A sample of known mass is heated or cooled in a small baking pan with the same but empty baking pan and the change in its heat capacity is tracked as a change in heat flow. This allows detection of transitions such as melting, glass transition, phase change and solidification. The greatest advantage of DSC is that it can be used to view the ease and speed of material transitions. In the glass transition zone where the material changes from a glassy form to a liquid form, there is an endothermic step change in the heat flow, and its midpoint (or starting point or inflection point) can be used to define the glass transition (Tg). All Tg values ​​mentioned herein are midpoint values, which are standard and well-known methods for those skilled in the field of polymer science.

[0052] The thermosetting epoxy functional (meth)acrylate resin may be free of or substantially free of hydroxyl functional groups.

[0053] The thermosetting epoxy functional (meth) acrylate resin may have an epoxy functionality / molecule (f / M) value of less than 14, such as less than 10. The thermosetting epoxy functional (meth) acrylate resin preferably has an f / M value of about 5-13.5, and in yet another embodiment the f / M value is about 8-10. The f / M value is calculated from Mw / EEW. Mw can be determined by gel permeation chromatography (GPC). EEW can be determined by the acetic acid / perchloric acid method (ASTM D 1652-04) using a Metrohm automatic titrator equipped with a 808 Titrando and 805 Dosimat device.

[0054] In some embodiments, the thermosetting epoxy functional (meth)acrylate resin has a weight average molecular weight (M) in the range of 2,000-20,000, preferably 2,000-10,000. w ). Unless otherwise indicated, the term "molecular weight" as used herein refers to the weight average molecular weight of a polymer as measured by gel permeation chromatography (GPC) calibrated with polystyrene standards.

[0055] The thermosetting epoxy functional (meth)acrylate resin can be formed by conventional polymerization methods in the presence of a thermal initiator or a redox initiator. Organic solvent polymerization can be performed. In other cases, aqueous emulsion polymerization can be performed.

[0056] The present invention also relates to a powder coating composition comprising the thermosetting epoxy functional (meth)acrylate resin described herein and a crosslinking agent capable of crosslinking with the resin.

[0057] For the avoidance of doubt, "crosslinking agent" refers to one or more crosslinking agents. The crosslinking agent comprises functional groups capable of reacting with the functional groups of the thermosetting epoxy functional (meth)acrylate resin. Preferred crosslinking agents are any crosslinking agents that react with epoxy groups without causing yellowing in the product coating, such as diacids or polyacids, anhydrides or dianhydrides.

[0058] Preferred crosslinking agents include organic dicarboxylic acids and their anhydrides, such as sebacic acid, adipic acid, azelaic acid and dodecanedioic acid, adducts prepared by esterification of polyesters or polyols to organic dicarboxylic acids or anhydrides, and polyisocyanates. The crosslinking agent can help improve the chipping resistance of the coating formed from the powder coating composition. Most preferably, the crosslinking agent comprises an acid functional crosslinking agent.

[0059] The amount of crosslinker in the powder coating composition may generally be in the range of 5 to 35 wt %, based on the total weight of the powder coating composition.

[0060] The powder coating composition may further comprise adjuvants, adhesion promoters, light stabilizers and ultraviolet (UV) absorbers or combinations thereof.

[0061] A suitable amount of adhesion promoter is in the range of about 0.1-10 wt %, preferably 0.2-3 wt %, based on the total weight of the powder coating composition. An amount greater than about 3 wt % may cause weathering problems. Most preferably, the amount of adhesion promoter is in the range of about 0.1-1 wt %. The adhesion promoter may comprise one or more epoxy resins, isocyanate compounds or T g Prepolymers with a temperature of 40° C. or higher, such as epoxy resins, epoxy-phenolic novolac resins, isophorone diisocyanate (IPDI), hexamethylene diisocyanate (HMDI) or toluene diisocyanate, blocked isocyanates such as caprolactam blocked dimers and trimers of IPDI, and isocyanate-terminated prepolymers of diisocyanates or dimers or trimers thereof with polyols or diols. Preferred adhesion promoters are bisphenol epoxy resins, more preferably bisphenol A or bisphenol F epoxy resins.

[0062] The additive may be a hydrophobic submicron particle to help resist filamentous corrosion. For example, the powder coating composition may further comprise about 0.1-1.5 wt % of hydrophobic submicron particles, such as inorganic oxides, such as metal oxides or silicon dioxide, and organic silicon compounds, such as polydimethylsiloxane (PDMS) treated fumed silica, based on the total weight of the powder coating composition.

[0063] Optionally, a hydrolyzable silane, such as an alkoxysilane, may also be used to couple fillers and inorganic oxide pigments to the coating matrix in an amount of about 0.01-3 wt %, preferably about 0.01-0.3 wt %, based on the total weight of the powder coating composition. Examples of suitable silanes include glycidyl alkoxysilanes and aminoalkoxysilanes, such as glycidyl trimethoxysilane.

[0064] Light stabilizers or ultraviolet (UV) absorbers can be used to help weather resistance. The light stabilizer or UV light absorber can be used in an amount of about 0.1-15 phr, preferably about 0.1-5 phr. Suitable light stabilizers include, for example, hindered amines, such as poly (alkanoyl piperidinol), such as oligomers of dimethyl succinate and 4-hydroxytetramethylpiperidinol, hindered phenols or combinations thereof; suitable UV light absorbers include, for example, benzotriazoles, oxalic acid diarylamide and 2-hydroxybenzophenone.

[0065] A small amount, for example, about 0.001-0.10 wt %, preferably about 0.001-0.05 wt %, of organic pigments, such as phthalocyanines, may be included to control yellowing. The powder coating composition may additionally comprise any of the following: about 0.001-1.0 wt % of a fluorescent brightener and / or a leveling agent, based on the total weight of the powder coating composition; about 0.1-10 phr of a flatting agent, such as (meth) alkyl acrylate copolymers, about 0.01-6 phr of wax, based on the total weight of the powder coating composition; and about 0.01-1.0 wt % of a post-blending additive, such as a dry flow aid such as silica and fumed alumina, based on the total weight of the powder coating composition.

[0066] The powder coating composition may comprise (at least) two different resins (copolymers) and a crosslinking agent capable of crosslinking with the resins (copolymers). That is, the powder coating composition may comprise the thermosetting epoxy functional acrylate resin of the present invention, a different resin and a crosslinking agent capable of crosslinking with the resin.

[0067] To prepare a powder coating composition comprising a resin mixture (copolymer), for example the resins may be mixed at any time after polymerization, or one resin may be copolymerized in the presence of an already formed resin.

[0068] Suitable resins / copolymers to be mixed with the thermosetting epoxy functional (meth)acrylate copolymer may be selected from various epoxy functional (meth)acrylate copolymers, epoxy functional vinyl copolymers, carboxylic acid functional acrylic copolymers, carboxylic acid functional vinyl copolymers and mixtures and combinations thereof.

[0069] Preferably, the resin mixed with the thermosetting epoxy-functional (meth)acrylate copolymer is a different (second) epoxy-functional (meth)acrylate copolymer. The second epoxy-functional (meth)acrylate copolymer may, for example, have a Tg greater than 50° C., 60° C., 70° C. or 80° C. The second epoxy-functional (meth)acrylate copolymer may have a weight average molecular weight greater than 2,000, for example between 2,000 and about 20,000.

[0070] For example, the powder coating composition may comprise two different thermosetting epoxy functional (meth)acrylate resins of the present invention and a crosslinker capable of crosslinking with the resins. Preferably, the two resins have a Tg greater than 40° C. Preferably, one or both resins have a Tg less than 80° C. Most preferably, one or both resins have a Tg greater than 50° C. and less than 70° C.

[0071] The powder coating composition is produced according to conventional methods. The components can be blended and then closely mixed, such as by melt compounding, so that no significant solidification occurs. The melt compound can be extruded and rapidly cooled after extrusion, then ground and, if necessary, the particulate matter is classified according to size. Optionally, in another embodiment the powder coating composition can be produced by combining particles comprising acrylic copolymers with hydrophobic submicron particles to form agglomerate particles.

[0072] The thermosetting epoxy functional (meth) acrylate resins described herein can be used to produce clear or pigmented clear powder coatings with excellent resistance to filamentary and CASS corrosion on aluminum or wrought alloy substrates, such as automotive wheel substrates, using conventional application techniques. The powder coating compositions can improve resistance to filamentary and CASS corrosion and have excellent appearance, good color and excellent blocking resistance. The powder coating compositions described herein provide coatings resistant to filamentary and CASS corrosion, which are used to coat the surfaces of iron, steel, magnesium alloys and brass substrates. The powder coating compositions can be hardened to form clear coatings.

[0073] The powder coating composition can be applied to a pretreated, precoated or bare metal substrate. Suitable substrates can include, for example, aluminum, wrought alloys, iron, steel, magnesium alloys, such as electronic products and brass, such as locks and door hardware. Aluminum substrates can include, for example, aluminum silicon alloys, aluminum lithium alloys, aluminum magnesium alloys, aluminum zinc alloys, aluminum manganese alloys, aluminum copper based alloys such as aluminum bronze, etc. The alloy can be single, binary or have two or more metals. Preferably, the substrate is pretreated. Aluminum and wrought alloy substrates can be pretreated with, for example, a self-assembled monolayer of phosphorus organic materials, zirconium titanate or acrylic modified zirconium titanate. Steel and iron substrates can be pretreated with passivators, such as zinc phosphate or iron phosphate. Particularly suitable substrates include aluminum wheels and automotive interiors. Preferably, the substrate is aluminum or a wrought alloy.

[0074] The present invention also relates to a coated substrate coated with a powder coating composition comprising the claimed thermosetting epoxy-functional (meth)acrylate resin and a crosslinking agent for the resin.

[0075] The powder coating composition can be hardened to form a clear coating.A clear coating is one that has a haze value of 70% or less when measured using a Rhopoint IQ (goniophotometer) according to ASTM D523 at a dry film thickness of 3 mils.

[0076] The powder coating composition may be applied via conventional equipment.For electrostatic coating, the average size of the particles may be in the range of about 5-200 μm, and in another embodiment from about 25 μm or more to about 75 μm or less.

[0077] Once the coating is applied, it is heat cured, for example, at a temperature of about 90-250° C. for a time of about 30 seconds to about 90 minutes. The heat for heat curing can come from convection, infrared (IR), or near IR sources.

[0078] The following examples are provided to illustrate embodiments of the thermosetting epoxy functional (meth)acrylate resins and powder coating compositions described herein and are not intended to limit the scope of the claimed invention. Example

[0079] Test Method

[0080] Dry film thickness Use POSITECTOR from DeFelsko Corporation, Ogdensburg, NY TM Model 6000-FN1 Coating Thickness Gauge, film thickness was measured according to ASTM D 1400-00 "Standard Test Method for Nondestructive Measurement of Dry Film Thickness of Nonconductive Coatings Applied to Nonferrous Metal Substrates", 2000. Film thickness was recorded as a range of three readings (low to high) measured in the center portion of the panel.

[0081] Powder coating applied to machined aluminum plate (obtained from Enkei Corporation, Act Tower 26FL 111-2, Itayamachi, Naka-ku, Hamamatsu-city, Shizuoka-prep, 430-7726, Japan) (cast aluminum alloy A356) Filiform corrosion resistance The test was conducted by cutting a scribe line perpendicular to the machined line through the coating down to the substrate (approximately 100 mm scribe length) using a hemispherical ruby ​​tip scribe tool / fixture (manufactured by Sheen Instruments) in accordance with SAE J2634, but with the following modifications: A continuity check was performed down the entire length of the scribe to ensure exposure down to the base metal. The test panel holder with the filiform corrosion test panel was moved at a constant speed of 3-4 cm / s with the ruby ​​tip positioned horizontally relative to the test panel. The test load was placed on the ruby ​​tip and fixed at a weight of 6600 g.

[0082] The scribed board was placed in a CASS chamber according to ASTM B 368-97 (2003) so that the board and the scribe were at an angle of approximately 45 degrees to the horizontal plane on the non-metallic support. Each board was exposed in the CASS box for 6 hours as described in ASTM B 368-97 (2003). After CASS, a vertical 90-degree oscillating rotational rinse with a 3-second constant flow of deionized water was performed on each board. Within 15 minutes of the rinse, each board was placed in a humidity chamber. All boards in the humidity chamber were placed so that water droplets flowed out of the section at approximately 45 degrees. Each board was exposed in the humidity chamber for 672 hours.

[0083] Each plate was assessed for maximum filament growth every 168 hours.The length of all filaments on each sample was measured with a metric ruler and the average creep (filament length) and maximum creep (longest filament length) were reported.

[0084] Wet Adhesion Measured according to ISO 4624 standard, but modified as follows: Approximately 1.3 g of powder are sprayed on a fully pre-treated test panel (6×4” and 6 mm thick) and then placed flat in an oven at 350° F. for 3 minutes until the coating becomes transparent. The test panel is removed from the oven and the flat surface of 6 pre-treated aluminum dollies, each with a circular cross-section and a diameter of 20 mm, are placed on the panel and returned to the oven for the remainder of the powder curing procedure. The cured test panel is removed from the oven and allowed to cool before being connected to a tensile tester, Positest ATM20 from Defelsko. The tensile stress is increased uniformly at a rate not greater than 1 MPa / s. The tensile stress at which each of the 6 dollies fails is recorded in MPa.

[0085] The same procedure was followed for wet adhesion until the test panel was fully cured, then placed in a humidity cabinet (60°C, 85% RH) for 28 days, then taken out and allowed to cool before connecting to a tensile tester, Positest ATM20 from Defelsko. The tensile stress was increased uniformly at a rate not greater than 1 MPa / s. The tensile stress at which each of the 6 dowels failed was recorded in MPa.

[0086] Diffusivity of image (DOI) and haze There are two parameters that can be used to assess the transparency of clear coatings. Use the RhopointIQ (goniophotometer), a handheld instrument that can measure these two parameters simultaneously by placing it directly on the cured clear coating and record the measurements in triplicate. When measuring DOI, a surface that displays a perfect, undistorted image returns a value of 100, and as this value decreases, the image becomes less discernible. When checking haze values, the opposite is true, as higher numbers indicate lower surface quality. When analyzing dry film thickness in an area of ​​3 mils, 70% is considered an acceptable level. Record the measurements in accordance with ASTM D523.

[0087] Glossiness. Clear coatings can also be defined by measuring gloss. Gloss is measured using a BYK micro-TRI gloss meter with a calibrated porcelain tray Cat# 4522 / 4527 or equivalent. The gloss of the cured film on an Al plate (AL-Q) is measured in accordance with ASTM D-523. Gloss parameters of 100+ and 110+ are required at 20° and 60°, respectively.

[0088] Tg Measured by Differential Scanning Calorimetry (DSC). DSC machine and operating details: Perkin Elmer Jade DSC with intercooler and nitrogen supply. Operation sequence: Cool to -50°C at 50°C / min; hold at -50°C for 5 minutes; heat from -50°C to 250°C at 20°C / min; cool from 250°C to -50°C at 50°C / min; hold at -50°C for 5 minutes; heat from -50°C to 150°C at 20°C / min; cool from 150°C to 20°C at 20°C / min. Tg data were collected from the second heating operation and quoted as the midpoint of the glass transition.

[0089] Resin Example 1—Epoxy-functional (meth)acrylate resin (Comparative example)

[0090] 500.1 g of n-butyl acetate was added to a 5-liter four-necked round-bottom glass reactor equipped with a mechanical stirrer, condenser, nitrogen inlet and bubbler, temperature measuring probe and monomer / initiator feed tube. The flask was heated under reflux (at about 125° C.) with a nitrogen atmosphere. The mixture of monomers and initiators was prepared by mixing 280 g (23.67 mol%) of glycidyl methacrylate, 150 g (8.11 mol%) of isobornyl methacrylate, 530 g (63.61 mol%) of methyl (meth)acrylate, 40 g (4.61 mol%) of styrene, 179.1 g of n-butyl acetate and 67 g of 21S (tert-butyl peroxy-2-ethylhexanoate) initiator was prepared by combining in a 5 liter container. The nitrogen flow to the reactor was turned off. The monomer and initiator mixture was fed into the reactor over a period of 3 hours while maintaining an internal temperature of 122-129°C. After the addition of the monomer and initiator mixture, 5.2 g of A second mixture of 21S in 57.1 grams of butyl acetate was added to the flask, again maintaining an internal temperature of 122-129°C. The reaction was maintained at approximately 125°C for an additional 45 minutes. The reactor setup was then changed from a reflux condenser to a distillation setup. The temperature was raised to 145-150°C to evaporate the solvent, which was then removed from the reactor mixture by distillation. Once the distillation was complete, the molten polymer was discharged into a tray and the residual solvent was removed in a vacuum oven at 150°C. The tray was then removed from the oven, the resin was allowed to cool to room temperature, and then crushed into solid particles. The resulting powder of Example 1 had a Tg (measured) of 62.6°C, an Mw of 5546, and an Mn of 2572.

[0091] Resin Examples 2 and 3—Epoxy-functional (meth)acrylate resins (invention)

[0092] Examples 2 and 3 were prepared in exactly the same manner as Comparative Example 1, except that 5 mol% or 10 mol% of MMA in Comparative Example 1 was replaced with the same mol% of VPADME (dimethyl vinylphosphonate) monomer in Examples 2 and 3, respectively. The amounts of monomers and initiators are shown in Table 1.

[0093] Table 1

[0094]

[0095] The powder of Example 2 had a Tg (measured) of 56.9°C, Mw of 5931, Mn of 2851, EEW of 560.2 and f / m of 10.6. The powder of Example 3 had a Tg (measured) of 59.5°C, Mw of 5473, Mn of 2672, EEW of 559.9 and f / m of 9.8.

[0096] Preparation of Coating Formulation Examples 4, 5 and 6

[0097] Powder coating formulation examples 4, 5 and 6 were formed from the components listed in Table 2 according to a method in which the raw ingredients were blended in a Prism mixer at 2000 rpm for 30 seconds and then extruded in a Thermo Prism TSE 24HC twin screw extruder at 400 rpm, 50-70% torque and 100°C (212°F) barrel temperature setting. The resulting molten extrudate was dropped onto a cooling plate and rolled into sheets and then pelletized in the form of chips. Post-blending (dry stream) additives were mixed with the chips by bag shaking for 0.25-0.5 minutes. The post-blending chips were then ground into a fine powder in a ZM laboratory mill (Retsch, Wuppertal-Haan, Germany) at 20,000 rpm using a 1.0 mm mesh size screen. The resulting milled powder was sieved through a 74 μm (200 mesh) size screen for subsequent application to form coatings and applied to the indicated substrates at the indicated thicknesses using a corona electrostatic spray gun and then cured in an electrically heated laboratory oven under a standard curing schedule.

[0098] Table 2

[0099]

[0100] 1. Sebacic acid, ICC Chemical Corp., Warrenville, IL.

[0101] 2. Mi Won benzoin, GCA Chemical Corp., Bradenton, FL.

[0102] 3. Resiflow TM PL 200, Estron Chemical, Calvert City, KY.

[0103] 4.UVAsorb TM HA22, 3V Inc, Charlotte, NC

[0104] 5. Tinuvin TM 405, BASF Pigments and Resins, Ludwigshafen, Germany.

[0105] 6. Ultranox TM 626, Addivant, Inc, Middlebury, CT.

[0106] 7. Irganox TM 1076, BASF Plastic Additives, Basel, Switzerland.

[0107] 8.Optiblanc TM PL, 3V Inc, Weehawken, NJ.

[0108] 9.Hostaperm TM 14-4006Violet RL SP, Clariant, Charlotte, NC.

[0109] 10.Xiameter TM OFS-6040 Silane, Dow Corning Corp., Midland, MI.

[0110] 11.Aeroxide TM C, Evonik Corp., Parsippany, NJ

[0111] Preparation and testing of coated aluminum substrates

[0112] The coated aluminum substrate was prepared in the following manner. A raw aluminum ingot of alloy A356 (produced by Enkei Corporation, ActTower 26FL 111-2, Itayamachi, Naka-ku, Hamamatsu-city, Shizuoka-prep, 430-7726, Japan) were cut into 6 mm thick plates with a size of 6×4” and then machined on one side using a lathe with a diamond tip having an approximate width of 350 microns for each machining line. The surface treatment of the aluminum plates was performed using a commercially available pretreatment in the following four stages in chronological order, with rinsing with deionized water between each step. Stages: mild alkaline cleaner, acidic deoxidizer solution, chromium-free conversion of zirconium titanate, and self-assembled monolayer of phosphorus organic material. Final drying at 100°C / 15 minutes in an electric oven was performed to ensure that the substrate was completely dry before packaging. The pretreated aluminum plates were then powder coated and cured for 25 minutes on the same day to achieve a substrate surface temperature of 176.6°C (350°F) to obtain a film thickness of 60-80 μm (approximately 2.0-3.0 mils).

[0113] Average filament length, wet adhesion, 20° gloss, 60° gloss, DOI and haze were measured for each coating. The results are shown in Table 3.

[0114] Table 3

[0115]

[0116]

[0117] Examples 5 and 6 show that polymers prepared using VPADME monomer provide significant improvements in filament corrosion resistance and wet adhesion without loss of clarity compared to the control epoxy functional (meth)acrylate copolymer of Example 1. The greater the amount of VPADME, the greater the improvement in filament corrosion resistance. The control formulation is similar to Powder Formulation 3 in US 9,834,634, which also contains a resin made from glycidyl methacrylate, isobornyl methacrylate, methyl (meth)acrylate, and styrene monomers but without dimethyl vinylphosphonate. The average filament length of Example 3 in US 9,834,634 is reported as 1.56 (also a poorer performance compared to Examples 5 and 6 of the present invention).

[0118] other

[0119] While particular embodiments of the invention have been illustrated and described herein, the invention is not intended to be limited to the details shown. Rather, various modifications may be made in the details within the range and equivalents of the claims without departing from the spirit and scope of the invention.

[0120] All phrases including brackets are meant to include either or both of the contents within the brackets and the contents not including the brackets. For example, the phrase "(co)polymer" includes polymers, copolymers and mixtures thereof in alternative forms.

[0121] Unless otherwise stated, all methods refer to and all examples were conducted under conditions of standard temperature and pressure (STP). Unless otherwise stated, all percentages are by weight.

[0122] All ranges described herein are inclusive and combinable. For example, if a component can be present in an amount of 0.05 wt % or greater to 1.0 wt % and in an amount of up to 0.5 wt %, then the component can be present in an amount of 0.05-1.0 wt %, 0.5-1.0 wt % or 0.05-0.5 wt %.

[0123] As used herein, the phrase "powder coating" refers to a coating formed from a powder coating composition.

[0124] As used herein, the term "phr" refers to the amount of ingredients per hundred parts by weight of the resin system, by weight. "Resin system" refers to the totality of the epoxy resin, toughening resin, and any crosslinking agent, curing agent, or hardener (but not catalyst) that becomes part of the crosslinked structure.

[0125] As used herein, the term "polymer" includes random, block, multiblock and graft copolymers and any mixtures or combinations thereof. The term "copolymer" shall refer to any polymer made from two or more different monomers. The term "copolymerization" shall refer to the polymerization process for preparing the copolymer. As used herein, the terms "resin" and "polymer" are interchangeable.

[0126] As used herein, the term "substantially free of (a specified) copolymerized monomer" means that the copolymer contains 2 weight percent or less of the specified copolymerized monomer, based on the total weight of copolymerized monomers.

Claims

1. A thermosetting epoxy-functional (meth)acrylate resin comprising the following monomers as copolymerizable monomers: i) 10-40 wt. % epoxy functional unsaturated monomers; ii) 10-20% by weight of alkyl (meth)acrylate monomers, wherein the alkyl group contains at least 6 carbon atoms, iii) 30-70% by weight of alkyl (meth)acrylate monomers, wherein the alkyl group contains 1-5 carbon atoms, iv) 0.5-40% by weight of dialkyl vinylphosphonate monomers, v) 1 to 50 wt. % vinyl aromatic monomers, and vi) 0-0.4% by weight of phosphonic acid monomers, The weight % of each monomer is based on the total weight of the copolymerized monomers in the resin.

2. The thermosetting epoxy-functional (meth)acrylate resin of claim 1, wherein the vinylphosphonic acid dialkyl ester monomer iv) comprises a phosphonic acid di-C1-C4 alkyl ester monomer.

3. The thermosetting epoxy-functional (meth)acrylate resin of claim 1, wherein the dialkyl vinylphosphonate monomer iv) comprises a dimethylphosphonate monomer.

4. The thermosetting epoxy-functional (meth)acrylate resin of claim 2, wherein the dialkyl vinylphosphonate monomer iv) comprises a dimethylphosphonate monomer.

5. The thermosetting epoxy-functional (meth)acrylate resin of claim 1, wherein the alkyl (meth)acrylate monomer ii) comprises a bicycloalkyl (meth)acrylate and / or a branched alkyl (meth)acrylate.

6. The thermosetting epoxy-functional (meth)acrylate resin of claim 2, wherein the alkyl (meth)acrylate monomer ii) comprises a bicycloalkyl (meth)acrylate and / or a branched alkyl (meth)acrylate.

7. The thermosetting epoxy-functional (meth)acrylate resin of claim 3, wherein the alkyl (meth)acrylate monomer ii) comprises a bicycloalkyl (meth)acrylate and / or a branched alkyl (meth)acrylate.

8. The thermosetting epoxy-functional (meth)acrylate resin of claim 4, wherein the alkyl (meth)acrylate monomer ii) comprises a bicycloalkyl (meth)acrylate and / or a branched alkyl (meth)acrylate.

9. The thermosetting epoxy functional (meth)acrylate resin of any one of claims 5 to 8, wherein the bicycloalkyl (meth)acrylate comprises isobornyl (meth)acrylate.

10. The thermosetting epoxy functional (meth)acrylate resin according to any one of claims 1 to 8, wherein the alkyl (meth)acrylate monomer iii) is selected from butyl (meth)acrylate and / or methyl methacrylate.

11. The thermosetting epoxy functional (meth)acrylate resin of claim 9, wherein the alkyl (meth)acrylate monomer iii) is selected from butyl (meth)acrylate and / or methyl methacrylate.

12. The thermosetting epoxy-functional (meth)acrylate resin of any one of claims 1 to 8, wherein the vinyl aromatic monomer v) comprises styrene.

13. The thermosetting epoxy-functional (meth)acrylate resin of claim 11, wherein the vinyl aromatic monomer v) comprises styrene.

14. The thermosetting epoxy-functional (meth)acrylate resin of any one of claims 1 to 8, wherein the epoxy-functional unsaturated monomer i) comprises a glycidyl ester of an α,β-ethylenically unsaturated carboxylic acid.

15. The thermosetting epoxy-functional (meth)acrylate resin of claim 13, wherein the epoxy-functional unsaturated monomer i) comprises a glycidyl ester of an α,β-ethylenically unsaturated carboxylic acid.

16. A powder coating composition comprising the thermosetting epoxy functional (meth)acrylate resin of any one of claims 1 to 15 and a crosslinking agent capable of crosslinking with the resin.

17. A powder coating composition according to claim 16, comprising two different thermosetting epoxy-functional (meth)acrylate resins according to any one of claims 1 to 15 and a crosslinking agent capable of crosslinking with said resins.

18. The powder coating composition of claim 16, wherein the crosslinking agent is an organic dicarboxylic acid, anhydride or an adduct thereof with a polyester or a polyisocyanate.

19. The powder coating composition of claim 17, wherein the crosslinking agent is an organic dicarboxylic acid, anhydride or an adduct thereof with a polyester or a polyisocyanate.

20. The powder coating composition of any one of claims 16 to 19, further comprising one or more adjuvants selected from the group consisting of hydrophobic submicron particles, adhesion promoters, light stabilizers, ultraviolet (UV) absorbers, and combinations thereof.

21. A coated substrate coated with a powder coating composition, wherein the powder coating composition comprises a thermosetting epoxy functional (meth)acrylate resin according to any one of claims 1 to 15 and a crosslinking agent for the resin.

22. The coated substrate of claim 21, wherein the substrate is aluminum or a wrought alloy.

Citation Information

Patent Citations

  • Powder coating composition based on epoxy containing polymers and polyacid curing agents

    US5407707A

  • Powder coating of epoxy-functional acrylic copolymer and polycarboxylic acid

    US5663240A

  • Epoxy functional acrylic coating powders and powder coatings therefrom having improved filiform corrosion resistance

    US8716367B2

  • Acrylic resins and powder coating compositions and powder coated substrates including the same

    US9834634B2

  • Acrylic resins and powder coating compositions and powder coated substrates including the same

    CN106029796A